Implementasi Program Kota Tanpa Kumuh (KOTAKU) di Kelurahan Tembilahan Hilir Kabupaten Indragiri Hilir - Robby Novrialdi; Sujianto Sujianto (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The City Without Slums Program (KOTAKU) is a nationally implemented program in 269 cities/regencies across 34 provinces, serving as a platform or basis for addressing slum areas by integrating various resources and funding sources, including those from the central government, provincial government, cities/regencies, donors, private sector, community, and other stakeholders. One of the areas where the KOTAKU program is implemented is Tembilahan Hilir Subdistrict. Tembilahan Hilir Subdistrict has the highest population density in Indragiri Hilir Regency, with a population of 79,178 people in 2020. Population density is one of the factors contributing to the formation of slum areas. The purpose of this study is to understand how the KOTAKU program is implemented in Tembilahan Hilir Subdistrict. The theoretical concept used is the policy implementation concept according to Charles O. Jones. The research method uses a qualitative approach with data collection techniques including observation, documentation, and interviews. The results of the study indicate that the implementation of the KOTAKU program in Tembilahan Hilir Subdistrict is carried out in accordance with the existing KOTAKU program implementation guidelines but cannot be fully executed due to budget constraints.